New 3003 Based Aluminium Alloy for Automotive Industry - Pavlasek, L.; Bernatik, M.; Szurman, I.; Kopelent, M. (Archives of Foundry Engineering, 2026)
It is estimated that up to 30 % of all human related green-house gases (GHGs) emissions in developed countries come from transport. Aluminium alloys are very popular materials for achieving weight reduction in new vehicles, thereby reducing fuel consumption and associated GHGs emissions. Unfortunately, the aluminium industry itself has a very harsh environmental impact. In order to achieve an overall GHGs emissions reduction, new aluminium alloys suitable for recycling need to be designed. The aim of this work is to present new fully recycled aluminium alloy for automotive applications based on modified composition of EN AW-3003 which allows higher impurity content. The microstructure and the mechanical properties of the new material are studied by optical microscopy and tensile tests in as-cast temper and as a 2.5 mm thick sheet in various heat treatment conditions. The results are compared with standard EN AW 3003 alloy and show that the properties of both alloys are relatively close.